DEVELOPMENT OF STUDENTS MOTIVATION TO THE DISTANCE LEARNING IN THE UNIVERSITIES - Lyashenko, Irina V. (Educological discourse, 2015)
In this article the mechanisms of students motivation in distance education in higher education are reviewed, the researches of modern domestic and foreign scientists on this issue are analyzed, the major practical recommendations for improving motivation in distance learning are highlighted.